Efficacy of N-acetylcysteine in Preventing Acute Kidney Injury and Major Adverse Cardiac Events After Cardiac Surgery: A Meta-Analysis and Trial Sequential Analysis - Zhao, Jingtao; Li, Maowei; Tan, Chen (Frontiers in Medicine, 2022)
Background The effect of N-acetylcysteine (NAC), an antioxidant, on preventing acute kidney injury (AKI) and major adverse cardiac events (MACE) remains controversial. Therefore, we conducted this meta-analysis and trial sequential analysis to evaluate its efficacy on cardiac surgery-related adverse events. Methods PubMed, Embase, and Cochrane Library were searched for relevant studies from inception to June 2021. We selected randomized controlled trials comparing NAC with controls in patients undergoing cardiac surgery. Results Twenty-five studies including 2,444 patients met the inclusion criteria. The pooled results showed that there was no significant difference in the incidence of AKI between the NAC and control groups [relative risk (RR) = 0.91, 95% confidence interval (CI) = 0.77, 1.08, P = 0.28], but the trial sequential analysis (TSA) could not confirm this result. No difference was observed in the need for renal replacement therapy (RRT), all-cause mortality, MACE, length of stay in the intensive care unit (ICU), and length of stay in the hospital. Results of subgroup analysis results showed that intravenous infusion instead of oral NAC could significantly reduce the incidence of AKI and arrhythmia (RR = 0.84, 95% CI = 0.71, 0.99, P = 0.03, I2 = 3% and RR = 0.74, 95% CI = 0.61, 0.91, P = 0.004, I2 = 48%, respectively). Conclusion Intravenous administration of NAC can reduce the incidence of AKI and arrhythmia in patients after cardiac surgery, but cannot reduce all-cause mortality, AMI, cardiac insufficiency, and the number of patients using RRT. Oral NAC has no significant effect on the outcomes of patients after cardiac surgery.